Persistent Umbilical Discharge from an Omphalomesenteric Duct Cyst Containing Gastric Mucosa - Kanimozhi Tamilselvan; Arunodaya Mohan; Sarah Cheslyn-Curtis; Michael Eisenhut (Case Reports in Pediatrics)
Umbilical discharge in infancy is often attributed to infection or an umbilical granuloma. It is important to investigate if such a discharge is due to an underlying congenital abnormality because corrective surgical intervention may then be required. We present the first case of an infant with a persistent umbilical discharge from an omphalomesenteric duct cyst. The discharge was associated with periumbilical dermatitis. The dermatitis was most likely due to irritation of the skin by gastric acid produced by the ectopic gastric mucosa contained in the omphalomesenteric duct cyst. Both discharge and dermatitis resolved after surgical removal of the cyst.